Accounting treatment of tax credits arising from the exclusion of ICMS from the PIS and COFINS calculation base of publicly traded companies - Douglas Willian Nascimento Schmidt; José Antonio Cescon; Antônio Carlos Brunozi Junior; Julio César Ferreira (Revista Ambiente Contábil)
Purpose: The objective of the study was to demonstrate the accounting treatment adopted by companies listed on B3, Novo Mercado, regarding the dispute over the exclusion of ICMS from the PIS and COFINS calculation basis, as well as demonstrating the change in accounting treatment, following the decision of the Federal Supreme Court, favorable to companies in 2017, modulated in 2021.